Competição e partição de nichos radiculares entre a palmeira babaçu (Attalea speciosa MART.) e o capim (Urochloa brizantha (Hochst ex. A. Rich) Stapf cv. ‘marandu’) em sistema silvipastoril na Amazônia maranhense - Pageú, André Brenner de Alencar (2021)
Much of the Legal Amazon in Maranhão is dominated by pastures with a large presence of genus (Urochloa spp.) with the palm tree Babaçu (Attalea speciosa MART). This combination constitutes a traditional silvopastoral system that offers the opportunity to investigate how two very competitive and widely distributed species interact in the soil. This research maps soil root profiles (0.5 m x1.0 m) in three silvopastoral systems in the eastern periphery of the Maranhão Amazon formed by Babaçu and Brachiaria (Urochloa brizantha (Hochst.ex.A.Rich) Stapf cv. 'marandu') in three treatments (distances) of dominance relative to the neck of the Babaçu palm: ‘inside’ Babaçu dominance' (0.4 - 0.6 m); 'medium distance' (2.50 - 6.0 m) and 'far – dominance of Urochloa' (8.0 - 10.00 m), accounting for three predefined diameter classes: 'thin' ((> 5 mm) for both species. The results showed a prevalence of fine superficial roots, with 74.6% concentrated in the layer (0 – 20 cm), and more abundant in the respective areas of dominance, with 48.07% of participation in the fine roots of "inside" babaçu, and 84.09% of participation of Urochloa in the "far" position. Medium and thick Urochloa roots were less expressive in all positions. But medium and thick babaçu roots were significant in vertical rooting in the “inside” position, with thick roots concentrating at 20 – 30 cm (P<0.0002). The vertical profiles of fine roots between Babaçu and Marandu grass differed, pointing to niche partitioning in the 0 – 10 cm range, with 41.9% of all Urochloa fine roots concentrated in the first 0 - 10 cm, as opposed to more rooting deeper of babaçu with 69.8 of the fine roots of babaçu between 10 - 50 cm. The vertical root profile of Urochloa was not affected by the treatment. However, the fine roots of babaçu escaped competition by rooting deeper in the Urochloa dominance point. It was concluded that the superficial limitation of Urochloa fine roots to the soil indicates a reduction in the ecological efficiency of Urochloa monospecific pastures. In contrast, deeper fine rooting of Babaçu indicates plasticity/niche expansion of the palm when in interspecific competition, improving the ecological efficiency of the system. This feature is likely a key component of Babaçu remarkable ecological success in degraded pastures in eastern Amazonia.